Alejandro F. Haber: Al otro lado del vestigio. Editorial Universidad del Cauca/JAS Arqueología/Ediciones del Signo, Popayán: 2016 - Tejerizo-García, Carlos (Complutum, 2019)
Haber, Alejandro F.: "Al otro lado del vestigio". Editorial Universidad del Cauca/JAS Arqueología/ Ediciones del Signo, Popayán: 2016